Bilingualism and Biliteracy in Down Syndrome: Insights From a Case Study. Issue 4 (1st June 2016) - Burgoyne, Kelly; Duff, Fiona J.; Nielsen, Dea; Ulicheva, Anastasia; Snowling, Margaret J.
Abstract: We present the case study of MB—a bilingual child with Down syndrome (DS) who speaks Russian (first language [L1]) and English (second language [L2]) and has learned to read in two different alphabets with different symbol systems. We demonstrate that, in terms of oral language, MB is as proficient in Russian as English, with a mild advantage for reading in English, her language of formal instruction. MB's L1 abilities were compared with those of 11 Russian‐speaking typically developing monolinguals and her L2 abilities to those of 15 English‐speaking typically developing monolinguals and six monolingual English‐speaking children with DS; each group achieving the same level of word reading ability as MB. We conclude that learning two languages in the presence of a learning difficulty need have no detrimental effect on either a child's language or literacy development. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible in the IRIS digital repository athttp://www.iris‐database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki .